Occurrence, associated factors and soft tissue reconstructive therapy for buccal soft tissue dehiscence at dental implants: Consensus report of group 3 of the DGI/SEPA/Osteology Workshop. (28th June 2022) - Guerrero, Adrián; Heitz‐Mayfield, Lisa J. A.; Beuer, Florian; Blanco, Juan; Roccuzzo, Mario; Ruiz‐Magaz, Vannesa; Sanz‐Martín, Ignacio; Schlee, Markus; Schliephake, Henning; Soetebeer, Maren; Sculean, Anton; Zabalegui, Ion; et al.
Abstract: Objectives: To systematically assess the literature and report on (1) the frequency of occurrence of buccal soft tissue dehiscence (BSTD) at implants, (2) factors associated with the occurrence of BSTD and (3) treatment outcomes of reconstructive therapy for the coverage of BSTD. Materials and Methods: Two systematic reviews addressing focused questions related to implant BSTD occurrence, associated factors and the treatment outcomes of BSTD coverage served as the basis for group discussions and the consensus statements. The main findings of the systematic reviews, consensus statements and implications for clinical practice and for future research were formulated within group 3 and were further discussed and reached final approval within the plenary session. Results: Buccally positioned implants were the factor most strongly associated with the risk of occurrence of BSTD, followed by thin tissue phenotype. At immediate implants, it was identified that the use of a connective tissue graft (CTG) may act as a protective factor for BSTD. Coverage of BSTD may be achieved with a combination of a coronally advanced flap (CAF) and a connective tissue graft, with or without prosthesis modification/removal, although feasibility of the procedure depends upon multiple local and patient‐related factors. Soft tissue substitutes showed limited BSTD coverage. Conclusion: Correct three‐dimensional (3D) positioning of the implant is of utmost relevance to prevent the occurrence of BSTD. If present, BSTD may be covered by CAF +CTG, however the evidence comes from a low number of observational studies. Therefore, future research is needed for the development of further evidence‐based clinical recommendations.